Design for 4D printing: Modeling and computation of smart materials distributions. (5th November 2019) - Sossou, Germain; Demoly, Frédéric; Belkebir, Hadrien; Qi, H. Jerry; Gomes, Samuel; Montavon, Ghislain
Abstract: The material complexity allowed by additive manufacturing (AM) has made smart materials (SMs) processing easier than usually, giving birth to the so called 4D printing (4DP). This has expanded further the design space around AM. Yet, for this design space to be embraced by designers, there is the need to make SMs modeling and simulation easier, especially in conceptual design. Previously, efforts have been dedicated to a voxel-based modeling and simulation framework for SMs showing how important are material distributions (MDs) when it comes to design for 4DP. Here, a twofold contribution is made to design for 4DP. First a computational tool embodying the previously developed theoretical framework is introduced. This tool – VoxSmart – harnesses the power and the convenience of the graphical algorithm editor Grasshopper® within the CAD software Rhinoceros® to SMs modeling and simulation. The tool basically allows for an easy simulation of any MD. Given a source shape and a target shape of the same part, a set of materials (conventional/smart) and a stimulus, finding the right MD that yields the appropriate transformation upon exposure to the stimulus is quite challenging. This is the core of the second contribution. An adaptive compliant wing of a micro unmanned aerial vehicle is presented as case study. Graphical abstract: Unlabelled Image Highlights: A computational design tool – VoxSmart – embodying a conceptual design framework for 4D printing is put forward. VoxSmart allows for modeling and simulation of heterogeneous objects made, among others, of shape changing smart materials. A material distribution (MD) computation engine is proposed to achieve prescribed shape changes upon exposure to stimulus. Similarly to how different genotypes express close phenotypes, it is found that different MDs can show the same shape change. An adaptive wing's case study with magnetostrictive materials is shown to illustrate the MD computation engine.